DISIPLIN APARATUR SIPIL NEGARA DALAM UPAYA PENINGKATAN KUALITAS PELAYANA PUBLIK - Sepa Erni (Universitas Tribhuwana Tunggadewi, 2019)
Abstract : Public services as the main pillar of implementing regional autonomy, the development of workdiscipline among the State Civil Apparatus indicated that work discipline influences the behavior ofemployees in order to improve the quality of sustainable public services. In order to create qualityservices, it is necessary to implement high employee discipline in efforts to achieve goals. The researchobjective was to find out the discipline of State civil apparatus as an effort to improve the quality ofpublic services in One Stop IntegratedService Investment and Manpower Agency of Batu in terms of thepublic service principles such as certainty, discipline, courtesy and hospitality, facilities andinfrastructure, security, simplicity of the service. This reseach is a qualitative research which aims tounderstand what phenomena are experienced naturally. The results of the study indicated that the OneStop IntegratedService Investment and Manpower Agency of Batu have tried to provide discipline to thecommunity through, completing their tasks on time, arriving at work on time, providing facilities thatsupport the community, discipline in providing security that can be seen from the coordination betweenemployees who always provide security, simplicity of the service and easily to be understood.Keywords: Public Service, Employee Discipline, State Civil ApparatusAbstrak: Pelayanan publik sebagai pilar utama penyelenggaraan otonomi daerah,pengembangan budayadisiplin kerja Aparatur Sipil Negara mengisyaratkan bahwa nilai budaya disiplin kerja mewarnai perilakupegawai dalam rangka meningkatkan kualitas pelayanan publik yang berkelanjutan. Dalam rangkamenciptakan pelayanan yang berkualitas dibutuhkannya penerapan disiplin pegawai yang tinggi dalamupaya pencapaian tujuan. Tujuan penelitian untuk mengetahui disiplin aparatur sipil Negara dalam upayapeningkatan kualitas pelayanan publik di Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu danTenaga Kerja Kota Batu ditinjau dari prinsip pelayanan publik yaitu kepastian waktu, tanggung jawab,kedisiplinan, kesopanan dan keramahan, kelengkapan sarana dan prasarana, keamanan, kesederhanaanpelayanan. Metode yang digunakan penelitian kualitatif, untuk memahami fenomena apa yang dialamisecara alamiah. Hasil penelitian menujukan bahwa Dinas Penanaman Modal Pelayanan Terpadu SatuPintu dan Tenaga Kerja Kota Batu sudah berupaya memberikan sikap disiplin kepada masyarakat melalui,pegawai menyelesaikan tugasnya dengan tepat waktu, pegawai datang tepat waktu untuk menerapkandisiplin pegawai, memberikan fasilitas yang menunjang kepada masyarakat, disiplin dalam memberikankeamanan dilihat dari koordinasi antar pegawai yang selalu memberikan pengaman, kesederhanaanpelayanan dalam memberikan pelayanan yang tidak berbelit-belit dan mudah dipahami.Kata Kunci : Pelayanan Publik, Disiplin Pegawai, Aparatur Sipil Negara